Over-expression of a Codon Optimized Yeast Cytosolic Pyruvate Carboxylase (PYC2) in CHO Cells for an Augmented Lactate Metabolism - Gupta, Sanjeev K.; Sharma, Ankit; Kushwaha, Hiralal; Shukla, Pratyoosh (Frontiers in Pharmacology, 2017)
Monoclonal antibodies are the most demanding biotherapeutic drugs now a days used for the cure of various critical illnesses. Chinese hamster ovary (CHO) cells are one of the main hosts used for the large scale production of these antibodies. However, the cell line and production processes are the key factors to determine the cost and affordability of these antibodies. The metabolic waste lactic acid and ammonium are accumulated during a cell culture process and adversely affects productivity as well as product quality. To control the lactate metabolism of mAb (IgG1-kappa) producing CHO clones, we super-transfected the cells with a mammalian construct bearing codon optimized yeast cytosolic pyruvate carboxylase (PYC2) and a strong fusion promoter for optimal expression of PYC2 enzyme. A pool study was also performed for the assessment of cell’s performance, post-translational modification of a mAb and its expression in a CHO clone. The current study resulted an improved mAb titer up to 5%, galactosylation up to 2.5folds, mannosylation up to 2 fold and marginal improved main and basic peaks in the charge variant profile at the cell pool stage. Such, approach may be suitable for the implementation in CHO cells producing recombinant protein for a better process control for the production of biotherapeutics.